The bodies left behind - Deaver, Jeffery (Simon & Schuster, 2008)
Arriving at a deserted lake house to investigate an aborted call to police, Deputy Anna McCafferty walks into the middle of a heinous crime and is deprived of her weapon, car, and phone, forced to flee, along with the twenty-five-year-old daughter of the murdered couple, into the surrounding forest to escape the perpetrators who must eliminate any potential witnesses.